2021
DOI: 10.1021/acs.inorgchem.1c01874
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Interlocked Superstructures with a Titanium Oxide Molecular Ring in Water

Abstract: [2]­Catenane, [2]­rotaxane, and [2]­pseudorotaxane based on a cyclic titanium oxide cluster, [Ti8O8(SO4)16]16– (Ti 8 ), and cyclic/linear alkylammonium cations are reported. Their syntheses, structures, spectroscopy, and stability in water were studied. These molecules were synthesized from and remained intact upon redissolution in acidic water. Hence, the cluster Ti 8 is a promising metal oxide ring that can be used as an inorganic analogue of crown ether to assemble inorganic–organic hybrid mechanical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Hence, the spectroscopic characteristics of a lyophilized solid sample may be utilized to deduce the speciation of solutes in the original solution. 22 Fig. 4 shows that the IR peaks of crystals of 1 at 1660, 1337, 1157, and 587 cm −1 are due to PA ligand, whereas those at 830, 758, and 690 cm −1 are attributable to Ti–O stretching vibrations.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, the spectroscopic characteristics of a lyophilized solid sample may be utilized to deduce the speciation of solutes in the original solution. 22 Fig. 4 shows that the IR peaks of crystals of 1 at 1660, 1337, 1157, and 587 cm −1 are due to PA ligand, whereas those at 830, 758, and 690 cm −1 are attributable to Ti–O stretching vibrations.…”
Section: Resultsmentioning
confidence: 98%
“…31 Jacobson et al and Wang et al reported [M 8 ] 16− (M = Cr and Fe) and [Ti 8 ] 16− with μ 2 -OH and μ 2 -SO 4 bridges. 32,33 (c) The cooperation between organic connectors and inorganic components constitutes a ring structure. Zhao et al reported on an Ln 7 ring constructed from 1,1′-cyclopropane-dicarboxylic acid and μ 3 -OH inorganic linkers (Ln = Gd and Dy).…”
Section: Introductionmentioning
confidence: 99%
“…25 Fu and Wang reported, respectively, that linear and cyclic amines can be hosted by Ti 8 wheel clusters to form pseudo-rotaxane or catenane-like structures. 26,27 Winpenny and co-workers isolated a family of cyclic [Ti x O (x+1) ] (x = 7, 8, or 9) clusters. The size of the rings was regulated by the alkylammonium cation, demonstrating the effect of the guests on host.…”
Section: ■ Introductionmentioning
confidence: 99%